KIRREL is differentially expressed in adipose tissue from 'fertil+' and 'fertil−' cows: in vitro role in ovary?. Issue 2 (February 2018) - Coyral-Castel, S; Ramé, C; Cognié, J; Lecardonnel, J; Marthey, S; Esquerré, D; Hennequet-Antier, C; Elis, S; Fritz, S; Boussaha, M; Jaffrézic, F; Dupont, J
Abstract : We have previously shown that dairy cows carrying the 'fertil−' haplotype for one quantitative trait locus affecting female fertility located on the bovine chromosome three (QTL-F-Fert-BTA3) have a significantly lower conception rate and body weight after calving than cows carrying the 'fertil+' haplotype. Here, we compared by Tiling Array the expression of genes included in the QTL-F-Fert-BTA3 in 'fertil+' and 'fertil−' adipose tissue one week after calving when plasma non-esterified fatty acid concentrations were greater in 'fertil−' animals. We observed that thirty-one genes were overexpressed whereas twelve were under-expressed in 'fertil+' as compared to 'fertil−' cows ( P  < 0.05). By quantitative PCR and immunoblot we confirmed that adipose tissue KIRREL mRNA and protein were significantly greater expressed in 'fertil+' than in 'fertil−'. KIRREL mRNA is abundant in bovine kidney, adipose tissue, pituitary, and ovary and detectable in hypothalamus and mammary gland. Its expression (mRNA and protein) is greater in kidney of 'fertil+' than 'fertil−' cows ( P  < 0.05). KIRREL (mRNA and protein) is also present in the different ovarian cells with a greater expression in granulosa cells of 'fertil+' than 'fertil−' cows. In cultured granulosa cells, recombinant KIRREL halved steroid secretion in basal state ( P  < 0.05). It also decreased cell proliferation ( P  < 0.05) and in vitro oocyte maturation ( P  < 0.05). These results were associated to a rapid increase in MAPK1/3 and MAPK14 phosphorylation in granulosa cells and to a decrease in MAPK1/3 phosphorylation in oocyte. Thus, KIRREL could be a potential metabolic messenger linking body composition and fertility.